Glass composition for dental use and composition for dental use

JP2025034538APending Publication Date: 2025-03-13GC CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023140970
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-31
Publication Date
2025-03-13

AI Technical Summary

Benefits of technology

【0007】 本発明の一態様によれば、得られる歯科用組成物の高いX線造影性と酸性物質共存下での保存安定性とを両立する歯科用ガラス組成物を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025034538000001
    Figure 2025034538000001
  • Figure 2025034538000002
    Figure 2025034538000002
  • Figure 2025034538000003
    Figure 2025034538000003
Patent Text Reader

Abstract

To provide a glass composition for dental use that ensures high X-ray contrast in the resulting dental composition while achieving storage stability in the coexistence of acidic substances.SOLUTION: A glass composition for dental use contains silicon (Si) and cesium (Cs) but is substantially free of sodium (Na), potassium (K), and alkaline earth metals.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a dental glass composition and a dental composition. [Background technology]

[0002] In the dental field, dental glass compositions containing barium are known as fillers (filling materials) to be mixed into dental hardenable compositions. Glass containing barium (barium glass) has high X-ray contrast properties, and is therefore widely used as a raw material for dental fillers that require X-ray contrast properties (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent No. 6346086 Summary of the Invention [Problem to be solved by the invention]

[0004] However, conventional barium-containing glasses contain polyvalent metals, and therefore in dental compositions in which acidic substances such as acidic group-containing polymerizable monomers are coexistent, the polyvalent metals and the acidic groups adsorb or react with each other, causing changes in paste properties and reduced adhesive strength, resulting in problems with storage stability.

[0005] An object of the present invention is to provide a dental glass composition which satisfies both high X-ray contrast properties and storage stability in the presence of an acidic substance. [Means for solving the problem]

[0006] A dental glass composition according to one embodiment of the present invention contains silicon (Si) and cesium (Cs) and is substantially free of sodium (Na), potassium (K) and alkaline earth metals. Effect of the Invention

[0007] According to one aspect of the present invention, a dental glass composition can be provided which has both high X-ray contrast properties and storage stability in the presence of an acidic substance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] Hereinafter, an embodiment of the present invention will be described in detail.

[0009] <Dental Glass Composition> The dental glass composition according to this embodiment contains silicon (Si) and cesium (Cs).

[0010] Silicon (Si) may be present in the dental glass composition as an oxide of silicon (Si), silicon oxide (SiO2).

[0011] The content of silicon (Si) is not particularly limited, and is, for example, preferably from 10% by mass to 80% by mass, more preferably from 20% by mass to 70% by mass, and even more preferably from 30% by mass to 60% by mass, calculated as the oxide in the dental glass composition.

[0012] By making the content of silicon (Si) calculated as oxide 10% or more by mass, it is possible to prevent the deterioration of the chemical durability of the glass and the devitrification. Also, by making the content of silicon (Si) calculated as oxide 80% or less by mass, it is possible to suppress the hardening of the glass melt, which makes it easy to adjust the viscosity of the dental glass composition and reduces the production cost.

[0013] Cesium (Cs) may exist in the dental glass composition as an oxide of cesium (CsO). Cesium (Cs) is an alkali metal with an atomic number (number of electrons) of 55, and exhibits high X-ray contrast in glass.

[0014] In this specification, X-ray contrast refers to the property whereby the shade of an X-ray image changes depending on the amount of X-ray absorption by the object, such as biological tissue or material, making it possible to visualize or distinguish the object.

[0015] In dental treatment, it is necessary to clarify the postoperative treatment area using dental materials such as dental filling materials, so such X-ray contrast is required for dental materials. In dental materials, the resin matrix is ​​an organic material and does not have sufficient X-ray contrast, so the filler made of inorganic materials such as glass is responsible for the X-ray contrast. Therefore, X-ray contrast is an important property for dental glass.

[0016] The cesium (Cs) content is not particularly limited, and is, for example, 5% by mass or more and 55% by mass or less, preferably 10% by mass or more and 45% by mass or less, and more preferably 20% by mass or more and 35% by mass or less, calculated as an oxide in the dental glass composition.

[0017] By making the content of cesium (Cs) calculated as oxide 5% or more by mass, the X-ray contrast property of the dental glass composition can be improved. Also, by making the content of cesium (Cs) calculated as oxide 55% or less by mass, the content of silicon (Si) in the dental glass composition can be secured and the decrease in chemical durability can be suppressed.

[0018] The dental glass composition of this embodiment may further contain boron (B), aluminum (Al), zirconium (Zr) and fluorine (F).

[0019] Boron (B) may be present in the dental glass composition as an oxide of boron (B), boron oxide (B2O3).

[0020] When boron (B) is contained, the content of boron (B) is not particularly limited, but is preferably from 1 to 45% by mass, more preferably from 5 to 35% by mass, and even more preferably from 10 to 25% by mass, calculated as the oxide in the dental glass composition.

[0021] By making the content of boron (B) calculated as oxide 1% or more by mass, the chemical durability of the dental glass composition is improved, the melting point of the glass melt is lowered, and the production can be facilitated. Also, by making the content of boron (B) calculated as oxide 45% or less by mass, the glass phase separation of the dental glass composition can be suppressed, and the deviation of the composition due to volatilization can be suppressed.

[0022] Aluminum (Al) may be present in the dental glass composition as an oxide of aluminum (Al), aluminum oxide (Al2O3).

[0023] When aluminum (Al) is contained, the content of aluminum (Al) is not particularly limited, and is, for example, preferably from 0.1% by mass to 35% by mass, more preferably from 0.5% by mass to 25% by mass, and even more preferably from 1% by mass to 15% by mass, calculated as the oxide in the dental glass composition.

[0024] By making the content of aluminum (Al) calculated as oxide 0.1% by mass or more, the chemical durability of the dental glass composition can be improved and devitrification of the glass can be suppressed. Also, by making the content of aluminum (Al) calculated as oxide 35% by mass or less, the melting point of the glass melt of the dental glass composition can be lowered, making it easier to manufacture.

[0025] Zirconium (Zr) may be present in the dental glass composition as an oxide of zirconium (ZrO2).

[0026] When zirconium (Zr) is contained, the content of zirconium (Zr) is not particularly limited, but is preferably 0.1 mass % or more and 20 mass % or less, more preferably 0.5 mass % or more and 15 mass % or less, and even more preferably 1 mass % or more and 10 mass % or less, calculated as an oxide.

[0027] By making the content of zirconium (Zr) calculated as oxide 0.1% by mass or more, the chemical durability of the glass can be improved, and the X-ray contrast property of the obtained glass can be improved. Also, by making the content of zirconium (Zr) calculated as oxide 20% by mass or less, the melting point of the glass melt of the dental glass composition can be lowered, and the production can be facilitated.

[0028] Fluorine (F) can be present in the dental glass composition as fluoride or a fluoride salt.

[0029] When fluorine (F) is contained, the content of fluorine (F) is not particularly limited, but is preferably 0.1 mass% or more and 10 mass% or less, more preferably 0.5 mass% or more and 8 mass% or less, and even more preferably 1 mass% or more and 5 mass% or less, in terms of simple fluorine (F).

[0030] By making the fluorine (F) content 0.1% by mass or more, the viscosity of the dental glass composition is reduced, the manufacturability of the dental glass composition can be improved, and the refractive index can be adjusted. Also, by making the fluorine (F) content 10% by mass or less, the devitrification of the glass can be suppressed, and the deviation of the composition due to volatilization can be suppressed.

[0031] The dental glass composition according to this embodiment is substantially free of sodium (Na), potassium (K) and alkaline earth metals.

[0032] In this specification, "substantially free" means that sodium (Na), potassium (K) and alkaline earth metals are not intentionally included, but unavoidable inclusion of these elements (unavoidable impurities) is permitted.

[0033] Sodium (Na) is an alkali metal with an atomic number (number of electrons) of 11, and is an element that easily reacts with acidic groups (such as phosphate groups). Potassium (K) is an alkali metal with an atomic number (number of electrons) of 19, and is an element that easily reacts with acidic groups (such as phosphate groups).

[0034] The alkaline earth metal is one or more elements selected from Be (beryllium), magnesium (Mg), calcium (Ca), strontium (Sr), and barium (Ba), all of which are elements that easily react with acidic groups (for example, phosphate groups).

[0035] The content of sodium (Na) permitted in the dental glass composition is 1 mass % or less, preferably 0.8 mass % or less, more preferably 0.5 mass % or less, calculated as oxide. The sodium (Na) permitted to be contained in the dental glass composition may exist as sodium oxide (Na2O) in the dental glass composition.

[0036] If the content of sodium (Na) in terms of oxide exceeds 1 mass%, sodium (Na) reacts with acidic groups (e.g., phosphate groups) and tends to cause poor storage stability in the paste. Therefore, it is preferable that sodium (Na) is substantially not contained.

[0037] In this specification, poor storage stability refers to a change in the properties of a paste obtained by mixing an acidic substance (eg, an acidic group-containing polymerizable monomer) with a dental glass composition.

[0038] The content of potassium (K) permitted in the dental glass composition is 1 mass % or less, preferably 0.8 mass % or less, more preferably 0.5 mass % or less, calculated as oxide. The potassium (K) permitted to be contained in the dental glass composition may exist as potassium oxide (KO) in the dental glass composition.

[0039] If the content of potassium (K) in terms of oxide exceeds 1 mass%, potassium (K) reacts with acidic groups (phosphate groups) and tends to cause poor storage stability in the paste. Therefore, it is preferable that potassium (K) is substantially not contained.

[0040] The allowable alkaline earth metal content in the dental glass composition is 1% by mass or less, preferably 0.8% by mass or less, and more preferably 0.5% by mass or less, calculated as the oxide.

[0041] The alkaline earth metals that are permitted to be contained in the dental glass composition may be present in the dental glass composition as oxides of the alkaline earth metals (e.g., beryllium oxide (BeO), magnesium oxide (MgO), calcium oxide (CaO), and strontium oxide (SrO).

[0042] If the content of alkaline earth metals in terms of oxides exceeds 1 mass %, the alkaline earth metals react with acidic groups (e.g., phosphate groups) and tend to cause poor storage stability in the paste, so it is preferable that the paste is substantially free of alkaline earth metals.

[0043] The alkaline earth metals that are substantially not contained in the dental glass composition are preferably calcium (Ca), strontium (Sr), and barium (Ba). Of the alkaline earth metals, calcium (Ca), strontium (Sr), and barium (Ba) are more likely to react with acidic groups (e.g., phosphate groups), and by substantially not containing these alkaline earth metals, it is possible to suppress poor storage stability in the paste.

[0044] The dental glass composition of the present embodiment may contain other elements as long as the object of the present invention is not impaired. Examples of other elements include zinc (Zn), tin (Sn), lanthanum (La), gadolinium (Gd), and rubidium (Rb) from the viewpoint of improving X-ray contrast and chemical durability, preventing devitrification, and facilitating production. The other elements may be present as oxides in the dental glass composition. The content of the other elements is not particularly limited, and they may be contained in the dental glass composition by any mass.

[0045] Zinc (Zn) may be present in the dental glass composition as an oxide of zinc (Zn), zinc oxide (ZnO).

[0046] When zinc (Zn) is contained, the content of zinc (Zn) is not particularly limited, but is preferably 0.1 mass % or more and 20 mass % or less, more preferably 0.5 mass % or more and 15 mass % or less, and even more preferably 1 mass % or more and 10 mass % or less, calculated as an oxide.

[0047] By making the content of zinc (Zn) calculated as oxide 0.1% by mass or more, the chemical durability of the dental glass composition can be improved and devitrification of the glass can be suppressed. Also, by making the content of zinc (Zn) calculated as oxide 20% by mass or less, devitrification can be prevented without decreasing the chemical durability of the obtained glass, and production can be facilitated.

[0048] Lanthanum (La) may be present in the dental glass composition as the oxide of lanthanum (La), lanthanum oxide (La2O3).

[0049] When lanthanum (La) is contained, the content of lanthanum (La) is not particularly limited, but is preferably 1 mass% or more and 40 mass% or less, more preferably 5 mass% or more and 35 mass% or less, and even more preferably 10 mass% or more and 30 mass% or less, calculated as an oxide.

[0050] By making the content of lanthanum (La) calculated as oxide 1% or more by mass, the X-ray contrast properties of the obtained glass can be improved, while by making the content of lanthanum (La) calculated as oxide 40% or less by mass, the meltability of the glass can be improved and the production can be facilitated.

[0051] Gadolinium (Gd) can exist as the oxide of gadolinium (Gd), gadolinium oxide (Gd2O3).

[0052] When gadolinium (Gd) is contained, the content of gadolinium (Gd) is not particularly limited, but is preferably 1 mass % or more and 30 mass % or less, more preferably 3 mass % or more and 25 mass % or less, and even more preferably 5 mass % or more and 20 mass % or less, calculated as an oxide.

[0053] By making the content of gadolinium (Gd) calculated as oxide 1% or more by mass, the X-ray contrast properties of the obtained glass can be improved, while by making the content of gadolinium (Gd) calculated as oxide 30% or less by mass, the meltability of the glass can be improved and the production can be facilitated.

[0054] Rubidium (Rb) may be present in the dental glass composition as an oxide of rubidium (Rb), rubidium oxide (RbO).

[0055] The content of rubidium (Rb) is not particularly limited, and is, for example, 3% by mass or more and 30% by mass or less, preferably 5% by mass or more and 25% by mass or less, and more preferably 8% by mass or more and 20% by mass or less, calculated as an oxide in the dental glass composition.

[0056] By making the content of rubidium (Rb) calculated as oxide 3% or more by mass, the X-ray contrast property of the dental glass composition can be improved, and the melting point of the glass melt of the dental glass composition can be lowered to facilitate production. In addition, by making the content of rubidium (Rb) calculated as oxide 30% or less by mass, the decrease in chemical durability can be suppressed.

[0057] The dental glass composition of this embodiment may contain other inevitable impurities, such as nickel (Ni).

[0058] The form of the dental glass composition is not particularly limited, and may be, for example, powder (or powder), plate, column, thread, or fiber. When the dental glass composition is in the form of powder, it becomes easy to blend or mix with each component of the dental composition, and the mechanical strength of the dental composition can be increased. When the dental glass composition is in the form of plate or column, the mechanical strength and transparency of the dental composition obtained when the dental glass composition is applied to a dental material can be improved.

[0059] When the dental glass composition is in the form of a powder, the particle size of the dental glass composition is not particularly limited, but is preferably 0.01 μm to 20 μm in median diameter, more preferably 0.02 μm to 10 μm in median diameter, and further preferably 0.1 μm to 1 μm in median diameter. Here, the particle size means the average particle size defined by the median diameter.

[0060] When the dental glass composition has a particle size of 0.01 μm or more, the dental glass composition is more easily handled when used as a powder, and when the dental glass composition has a particle size of 20 μm or less, the dental glass composition has improved mechanical strength when used in a dental material.

[0061] The dental glass composition of the present embodiment can provide a glass containing the composition with an X-ray contrast property of 300% or more, preferably 400% or more, and more preferably 450% or more, relative to aluminum. In this specification, the X-ray contrast property refers to the X-ray contrast property measured by a test method for X-ray contrast property of dental materials in accordance with ISO 4049:2019.

[0062] In this embodiment, the X-ray contrast property of the glass containing the dental glass composition is 210% or more relative to aluminum, so that a dental glass composition exhibiting good X-ray contrast property can be provided. The upper limit of the X-ray contrast property is not particularly limited, but is preferably 1000% or less relative to aluminum as a feasible range, more preferably 900% or less, and even more preferably 800% or less.

[0063] As described above, the dental glass composition of the present embodiment contains silicon (Si) and cesium (Cs) and is substantially free of sodium (Na), potassium (K) and alkaline earth metals, and thus the dental composition when applied to a dental material can achieve both high X-ray contrast properties and storage stability in the presence of acidic substances.

[0064] Furthermore, as described above, the dental glass composition of this embodiment is substantially free of alkaline earth metals calcium (Ca), strontium (Sr), and barium (Ba), and therefore, poor storage stability in a paste containing the dental glass composition can be suppressed.

[0065] <Dental Composition> The dental composition according to this embodiment contains the dental glass composition according to this embodiment described above and an acidic group-containing polymerizable monomer.

[0066] The acidic group-containing polymerizable monomer has a function of improving adhesion to dentin, ceramics such as zirconia and alumina, which are materials for dental restorations, and alloys containing precious metals. The acidic group-containing polymerizable monomer is not particularly limited, but examples thereof include (meth)acrylates having an acid group.

[0067] The (meth)acrylate monomer having an acid group is not particularly limited, and is, for example, a (meth)acrylate monomer having an acid group such as a phosphoric acid group, a pyrophosphoric acid group, a thiophosphoric acid group, a carboxy group, an acid anhydride residue, a sulfonic acid group, a phosphonic acid group, etc. The (meth)acrylate having an acid group may have a plurality of acid groups.

[0068] Examples of the (meth)acrylate having a phosphoric acid group include 2-(meth)acryloyloxyethyl dihydrogen phosphate, bis[2-(meth)acryloyloxyethyl]hydrogen phosphate, 2-(meth)acryloyloxyethyl phenyl hydrogen phosphate, 6-(meth)acryloyloxyhexyl dihydrogen phosphate, 6-(meth)acryloyloxyhexyl phenyl hydrogen phosphate, 10-(meth)acryloyloxydecyl dihydrogen phosphate, 1,3-di(meth)acryloylpropane-2-dihydrogen phosphate, 1,3-di(meth)acryloylpropane-2-phenyl hydrogen phosphate, and bis[5-{2-(meth)acryloyloxyethoxycarbonyl}heptyl]hydrogen phosphate.

[0069] Examples of (meth)acrylates having a pyrophosphate group include bis[2-(meth)acryloyloxyethyl] pyrophosphate, bis[4-(meth)acryloyloxybutyl] pyrophosphate, bis[6-(meth)acryloyloxyhexyl] pyrophosphate, bis[8-(meth)acryloyloxyoctyl] pyrophosphate, and bis[10-(meth)acryloyloxydecyl] pyrophosphate.

[0070] Examples of the (meth)acrylate having a thiophosphate group include 2-(meth)acryloyloxyethyl dihydrogen thiophosphate, 3-(meth)acryloyloxypropyl dihydrogen thiophosphate, 4-(meth)acryloyloxybutyl dihydrogen thiophosphate, 5-(meth)acryloyloxypentyl dihydrogen thiophosphate, 6-(meth)acryloyloxyhexyl dihydrogen thiophosphate, 7-(meth)acryloyloxyheptyl dihydrogen thiophosphate, 8-(meth)acryloyloxyoctyl dihydrogen thiophosphate, 9-(meth)acryloyloxynonyl dihydrogen thiophosphate, 10-(meth)acryloyloxydecyl dihydrogen thiophosphate, and 11-(meth)acryloyloxyundecyl dihydrogen thiophosphate. Examples of suitable acryloyloxyalkyl dihydrogen thiophosphate include 12-(meth)acryloyloxydodecyl dihydrogen thiophosphate, 13-(meth)acryloyloxytridecyl dihydrogen thiophosphate, 14-(meth)acryloyloxytetradecyl dihydrogen thiophosphate, 15-(meth)acryloyloxypentadecyl dihydrogen thiophosphate, 16-(meth)acryloyloxyhexadecyl dihydrogen thiophosphate, 17-(meth)acryloyloxyheptadecyl dihydrogen thiophosphate, 18-(meth)acryloyloxyoctadecyl dihydrogen thiophosphate, 19-(meth)acryloyloxynonadecyl dihydrogen thiophosphate, and 20-(meth)acryloyloxyicosyl dihydrogen thiophosphate.

[0071] Examples of (meth)acrylates having a carboxy group include 2-methacryloyloxyethyl succinic acid, 4-(meth)acryloyloxyethyl trimellitic acid, 4-(meth)acryloyloxydecyl trimellitic acid, 11-(meth)acryloyloxy-1,1-undecanedicarboxylic acid, 1,4-di(meth)acryloyloxypyromellitic acid, 2-(meth)acryloyloxyethyl maleic acid, 2-(meth)acryloyloxyethyl phthalic acid, and 2-(meth)acryloyloxyethyl hexahydrophthalic acid.

[0072] Examples of the (meth)acrylate having an acid anhydride residue include 4-(meth)acryloyloxyethyl trimellitic anhydride, 4-(meth)acryloyloxydecyl trimellitic anhydride, and the like.

[0073] Examples of the (meth)acrylate having a sulfonic acid group include 2-(meth)acrylamide-2-methylpropanesulfonic acid, styrenesulfonic acid, and 2-sulfoethyl (meth)acrylate.

[0074] Examples of the (meth)acrylate having a phosphonic acid group include 2-(meth)acryloyloxyethyl phenyl phosphonate, 5-(meth)acryloyloxypentyl-3-phosphonopropionate, 6-(meth)acryloyloxyhexyl-3-phosphonopropionate, 10-(meth)acryloyloxydecyl-3-phosphonopropionate, 6-(meth)acryloyloxyhexyl-3-phosphonoacetate, and 10-(meth)acryloyloxydecyl-3-phosphonoacetate.

[0075] These (meth)acrylate monomers having an acid group may be used alone or in combination of two or more.

[0076] As the (meth)acrylate having an acid group, from the viewpoints of the solubility of the smear layer on the tooth surface of the dental composition, the demineralization of tooth tissue, and in particular, the adhesion to enamel, a (meth)acrylate having a phosphate group, a thiophosphate group, a carboxy group, or an acid anhydride residue is preferred, and among these, a phosphate group is more preferred.

[0077] Furthermore, among these, 10-methacryloyloxydecyl dihydrogen phosphate (MDP), 10-methacryloyloxydecyl dihydrogen thiophosphate (MDTP), 4-methacryloyloxyethyl trimellitic anhydride (4-META), etc. are preferred in terms of improving the adhesion of the dental composition, with MDP being more preferred.

[0078] The content of the acidic group-containing polymerizable monomer in the dental composition is not particularly limited and can be, for example, 0.1% by mass or more and 20% by mass or less, preferably 1% by mass or more and 15% by mass or less, and more preferably 3% by mass or more and 10% by mass or less.

[0079] When the content of the acidic group-containing polymerizable monomer in the dental composition is 0.1% by mass or more, the adhesion of the dental composition to tooth structure is improved, and when the content is 20% by mass or less, the hardening property of the dental composition is improved.

[0080] The dental composition of the present embodiment may contain other components as long as the purpose of the present invention is not impaired. Examples of other components contained in the dental composition include a polymerizable monomer having no acid group, a polymerization initiator, a polymerization inhibitor, a filler, and a solvent. Examples of the polymerization initiator include a chemical polymerization initiator and a photopolymerization initiator.

[0081] The polymerizable monomer having no acid group is not particularly limited, and examples thereof include polyfunctional (meth)acrylate compounds, among which bifunctional (meth)acrylate compounds are preferred, such as ethoxylated bisphenol A dimethacrylate, 2,2-bis[4-[2-hydroxy-3-(methacryloyloxy)propyloxy]phenyl]propane, neopentyl glycol dimethacrylate, di-2-methacryloyloxyethyl 2,2,4-trimethylhexamethylene dicarbamate (UDMA), triethylene glycol dimethacrylate (TEGDMA), etc. These bifunctional (meth)acrylate compounds may be used alone or in combination of two or more.

[0082] The content of the polymerizable monomer not having an acid group in the dental composition is not particularly limited, and can be, for example, 1% by mass or more and 40% by mass or less in the dental composition, preferably 3% by mass or more and 35% by mass or less, and more preferably 5% by mass or more and 33% by mass or less.

[0083] When the content of the polymerizable monomer not having an acid group in the dental composition is 1 mass % or more, the adhesiveness of the dental composition can be improved, and when the content of the polymerizable monomer not having an acid group in the dental composition is 40 mass % or less, the acid reactivity of the dental glass composition in the dental composition can be suppressed, and poor storage stability in the paste can be suppressed.

[0084] The polymerization initiator is not particularly limited, and examples thereof include a chemical polymerization initiator and a photopolymerization initiator.

[0085] The chemical polymerization initiator is not particularly limited, and for example, a thiourea derivative, a vanadium compound, a tertiary amine, or an organic peroxide can be used.

[0086] Among chemical polymerization initiators, the thiourea derivatives function as reducing agents.

[0087] The thiourea derivative is not particularly limited, and examples thereof include ethylenethiourea, N-methylthiourea, N-ethylthiourea, N-propylthiourea, N-butylthiourea, N-laurylthiourea, N-phenylthiourea, N-cyclohexylthiourea, N,N-dimethylthiourea, N,N-diethylthiourea, N,N-dipropylthiourea, N,N-dibutylthiourea, N,N-dilaurylthiourea, N,N-diphenylthiourea, N,N-dicyclohexylthiourea, trimethylthiourea, tetramethylthiourea, N-acetylthiourea, N-benzoylthiourea, 1-allyl-3-(2-hydroxyethyl)-2-thiourea, 1-(2-tetrahydrofurfuryl)-2-thiourea, N-tert-butyl-N'-isopropylthiourea, and 2-pyridylthiourea.

[0088] These thiourea derivatives may be used alone or in combination of two or more. Among these, N-benzoylthiourea is preferred from the viewpoint of improving the hardening property of the dental composition.

[0089] The content of the thiourea derivative in the dental composition is not particularly limited, but is preferably 0.1% by mass or more and 5% by mass or less, more preferably 0.1% by mass or more and 3% by mass or less, and even more preferably 0.1% by mass or more and 1% by mass or less. When the content of the thiourea derivative in the dental composition is 0.1% by mass or more, the hardening property of the dental composition is further improved, and when it is 5% by mass or less, the solubility of the thiourea derivative in (meth)acrylate in the dental composition is improved.

[0090] The vanadium compound functions as a reducing agent among chemical polymerization initiators.

[0091] The vanadium compound is not particularly limited, and examples thereof include oxovanadium oxalate, vanadyl acetylacetonate, vanadium acetylacetonate, vanadyl stearate, vanadium naphthenate, vanadium benzoylacetonate, etc. These vanadium compounds may be used alone or in combination of two or more. Among these, vanadyl acetylacetonate is preferred from the viewpoint of hardening property of dental composition.

[0092] The content of the vanadium compound in the dental composition is not particularly limited, but is preferably 0.001% by mass or more and 5% by mass or less, more preferably 0.0015% by mass or more and 1% by mass or less, and even more preferably 0.002% by mass or more and 0.1% by mass or less. When the content of the vanadium compound in the dental composition is 0.001% by mass or more, the hardening property of the dental composition is further improved, and when it is 5% by mass or less, the storage stability of the dental composition is further improved.

[0093] Tertiary amines function as reducing agents among chemical polymerization initiators.

[0094] The tertiary amine is not particularly limited, and examples thereof include tertiary aliphatic amines and tertiary aromatic amines.

[0095] Examples of tertiary aliphatic amines include N,N-dimethylaminoethyl methacrylate and triethanolamine.

[0096] Examples of tertiary aromatic amines include alkyl p-dialkylaminobenzoates, 7-dimethylamino-4-methylcoumarin, N,N-dimethylaniline, N,N-dibenzylaniline, N,N-dimethyl-p-toluidine, N,N-diethyl-p-toluidine, N,N-bis(2-hydroxyethyl)-p-toluidine, N,N,2,4,6-pentamethylaniline, N,N,2,4-tetramethylaniline, and N,N-diethyl-2,4,6-trimethylaniline.

[0097] Of these, the tertiary amine is preferably a tertiary aromatic amine, and more preferably an alkyl p-dialkylaminobenzoate.

[0098] Examples of the alkyl p-dialkylaminobenzoate include methyl p-dimethylaminobenzoate, ethyl p-dimethylaminobenzoate, propyl p-dimethylaminobenzoate, amyl p-dimethylaminobenzoate, isoamyl p-dimethylaminobenzoate, ethyl p-diethylaminobenzoate, and propyl p-diethylaminobenzoate.

[0099] These tertiary amines may be used alone or in combination of two or more kinds.

[0100] Among the chemical polymerization initiators, the organic peroxide functions as an oxidizing agent.

[0101] Examples of organic peroxides include benzoyl peroxide, cumene hydroperoxide, t-butyl hydroperoxide, t-amyl hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, 2,5-dimethyl-2,5-di(hydroperoxy)hexane, p-diisopropylbenzene monohydroperoxide, p-methane hydroperoxide, and pinane hydroperoxide.

[0102] These organic peroxides may be used alone or in combination of two or more. Among these, cumene hydroperoxide is preferred from the viewpoint of hardening properties of the dental composition.

[0103] The content of the organic peroxide in the dental composition is not particularly limited, but is preferably 0.01% by mass or more and 10% by mass or less, more preferably 0.05% by mass or more and 5% by mass or less, and even more preferably 0.1% by mass or more and 3% by mass or less. When the content of the organic peroxide in the dental composition is 0.01% by mass or more, the hardening property of the dental composition is further improved, and when it is 10% by mass or less, the operation time of the dental composition is extended.

[0104] The photopolymerization initiator is not particularly limited, and examples thereof include camphorquinone (CQ), ethyl 4-dimethylaminobenzoate (EPA), 2,4,6-trimethylbenzoyldiphenylphosphine oxide (TPO), phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, benzil ketal, diacetyl ketal, benzil dimethyl ketal, benzil diethyl ketal, benzil bis(2-methoxyethyl)ketal, 4,4'-dimethyl(benzyl dimethyl ketal), anthraquinone, 1-chloroanthraquinone, 2-chloroanthraquinone, 1,2-benzanthraquinone, 1-hydroxyanthraquinone, 1-methylanthraquinone, 2-ethylanthraquinone, 1 ... Examples of such thioxanthone include anthraquinone, 1-bromoanthraquinone, thioxanthone, 2-isopropylthioxanthone, 2-nitrothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone, 2,4-diisopropylthioxanthone, 2-chloro-7-trifluoromethylthioxanthone, thioxanthone-10,10-dioxide, thioxanthone-10-oxide, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin isobutyl ether, benzophenone, bis(4-dimethylaminophenyl)ketone, and 4,4'-bis(diethylamino)benzophenone.

[0105] These photopolymerization initiators may be used alone or in combination of two or more. Among these, camphorquinone (CQ), ethyl 4-dimethylaminobenzoate (EPA), and 2,4,6-trimethylbenzoyldiphenylphosphine oxide (TPO) are preferred from the viewpoint of improving the hardening property of the dental composition.

[0106] The content of the photopolymerization initiator in the dental composition is not particularly limited, but is preferably 0.01% by mass or more and 5% by mass or less, more preferably 0.05% by mass or more and 3% by mass or less, and even more preferably 0.1% by mass or more and 1% by mass or less. When the content of the photopolymerization initiator in the dental composition is 0.01% by mass or more, the hardening property of the dental composition is improved, and when it is 5% by mass or less, the storage stability of the dental composition is improved.

[0107] Examples of the polymerization inhibitor include dibutylhydroxytoluene (2,6-di-tert-butyl-p-cresol), 6-tert-butyl-2,4-xylenol, and 1,4-dihydroxybenzene.

[0108] These polymerization inhibitors may be used alone or in combination of two or more. Among these, dibutylhydroxytoluene and 6-tert-butyl-2,4-xylenol are preferred from the viewpoint of improving the hardening property of the dental composition.

[0109] The content of the polymerization inhibitor in the dental composition is not particularly limited, but is preferably 0.001% by mass or more and 5% by mass or less, more preferably 0.005% by mass or more and 3% by mass or less, and even more preferably 0.01% by mass or more and 1% by mass or less. When the content of the polymerization inhibitor in the dental composition is 0.001% by mass or more, the storage stability of the dental composition is improved, and when the content of the polymerization inhibitor in the dental composition is 5% by mass or less, the hardening property of the dental composition is improved.

[0110] The filler is an inorganic filler, and examples of the filler include glass, a glass composition, a dental glass composition, and inorganic crystals.

[0111] As described above, the dental composition of this embodiment contains the dental glass composition of this embodiment, and therefore the effects of the dental glass composition can be obtained. That is, the dental composition containing the dental glass composition of this embodiment can achieve both high X-ray contrast and storage stability in the presence of an acidic substance. In addition, the dental composition of this embodiment exhibits good X-ray contrast, and therefore the repaired area can be clearly identified in diagnosis or examination using X-ray images after treatment.

[0112] The dental composition of the present embodiment is not particularly limited in its use, but since the dental composition exhibits high X-ray contrast, it can be used as a dental material that requires X-ray contrast. Examples of such dental materials include dental composite resins, dental cements, dental adhesives, dental temporary sealing materials, dental primers, dental coating materials, dental hard resins, dental cutting resin materials, dental temporary restorative materials, dental filling materials, and dentifrices. EXAMPLES

[0113] The present invention will be further described below with reference to examples. In the following, numerical values ​​without units or "%" are based on mass (% by mass) unless otherwise specified.

[0114] <Glass preparation> Glasses (glasses 1 to 8) were prepared with the compositions shown in Table 1. The glasses were obtained as bulk bodies by placing a raw material batch obtained by mixing various raw materials into a platinum crucible, then placing it in an electric furnace preheated to 1400 to 1600°C for 30 to 60 minutes, and pouring it into a carbon mold. Alternatively, after melting in the same manner, the glass melt was dropped into a water tank to obtain granulated glass. The glasses were pulverized in an alumina magnetic mortar to obtain glass powder with a median diameter (average particle size) of 20 to 300 μm.

[0115] The obtained glass bulk was heat-treated in an electric furnace by heating it from room temperature to 600°C at a heating rate of 20°C / min, holding it at 600°C for 30 minutes, and then slowly cooling it to room temperature. The heat-treated glass bulk was sliced ​​to obtain slices.

[0116] <Radiopacity> For the obtained glass slice pieces, the radiopacity (relative to Al%) was measured. The radiopacity was measured by the radiopacity test method for dental materials in accordance with ISO 4049:2019. Specifically, the optical density or gray value of a test piece (plate-shaped dental glass composition) with a thickness Ts (unit: mm) was measured. Next, the thickness Ta (unit: mm) of an aluminum plate showing the same optical density or gray value as the test piece with a thickness Ts was determined. Then, the ratio of Ta to Ts (unit: relative to Al%) was used as the value of radiopacity. The results of radiopacity are shown in Table 1.

[0117] Note that the silica filler described below could not form a bulk body due to being a powdery sample, and thus the accurate radiopacity could not be measured.

[0118]

Table 1

[0119] <Preparation of Dental Composition (Specimen)> The glass shown in Table 1 or silica filler (manufactured by Tatsumori Co., Ltd., RAF1000) was mixed and stirred using 3-methacryloxypropyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd.) as a silane treatment agent, and subjected to silane treatment to obtain an inorganic filler. Also, a polymerizable monomer (polymerizable monomer having no acid group), an acidic substance (polymerizable monomer containing an acidic group), a polymerization initiator, and an inhibitor were kneaded at the mass ratios shown in Table 2 to prepare an organic component.

[0120] Each of the obtained inorganic fillers was mixed with Aerosil (manufactured by Nippon Aerosil Co., Ltd.) and the organic components shown in Table 2, and a dental composition (specimen) was prepared at the compounding ratios shown in Table 3. In Table 3, Glass 1 to 5, 7, and 8 were mixed at compounding ratio 1, Glass 6 was mixed at compounding ratio 2, and the silica filler was mixed at compounding ratio 3, respectively.

[0121]

Table 2

[0122] The abbreviations for the components in Table 2 and their corresponding components are as follows: TEGDMA: Triethylene glycol dimethacrylate UDMA: Urethane dimethacrylate MDP: 10-methacryloyloxydecyl dihydrogen phosphate CQ: Camphorquinone EPA: Ethyl 4-dimethylaminobenzoate IA: 6-tert-butyl-2,4-xylenol BHT: Dibutyl hydroxytoluene

[0123] [Table 3]

[0124] <Storage stability test> A storage stability test was performed on the obtained dental composition (test specimen) to confirm the storage stability. The obtained dental composition (test specimen) was filled into a filling syringe and stored in a thermo-hygrostat at 37°C and 90% RH. In addition, water (0.8%) equivalent to storage at 37°C, 90% RH, and 3 months was added to the paste immediately after production. The dental composition (test specimen) immediately after production or after the addition of water was polymerized by light irradiation to obtain a hardened product of the dental composition (test specimen) (hardened dental composition).

[0125] <Evaluation criteria for storage stability> The storage stability of the dental composition (test specimen) immediately after production or after the storage stability test was judged by the following two methods. The viscosity of the dental composition (test specimen) was evaluated using a rheometer. If the viscosity (mPa·s) of the dental composition (test specimen) after the storage stability test increased by 10% or more compared to that immediately after production, the storage stability was judged to be poor. In addition, if the formation of an acidic substance (MDP) and a salt derived from glass eluate (detected as a needle-shaped substance in the SEM image) was confirmed by scanning electron microscope (SEM) observation of the hardened body (dental composition hardened body) hardened by photopolymerization, the storage stability was judged to be poor. Furthermore, if no defects were found in either SEM observation or rheometer evaluation, the storage stability was judged to be good, and if defects were confirmed in either one, the storage stability was judged to be poor. The evaluation results of the storage stability test are shown in Table 4.

[0126] <Measurement of X-ray contrast property of hardened dental composition> The X-ray contrast (% relative to Al) of the hardened product (hardened product of dental composition) obtained by hardening the dental composition (test specimen) by photopolymerization was measured. The X-ray contrast was measured by a method for testing the X-ray contrast of dental materials in accordance with ISO 4049:2019. Specifically, the optical density or gray value of a test specimen (hardened product of dental composition) having a thickness Ts (unit: mm) was measured. Next, the thickness Ta (unit: mm) of an aluminum plate showing the same optical density or gray value as the test specimen having a thickness Ts was determined. The ratio of Ta to Ts (unit:% relative to Al) was used as the value of X-ray contrast. In addition, in the hardened product of the dental composition, if the X-ray contrast (unit:% relative to Al) was 200 or less, it was judged to be inappropriate.

[0127] [Table 4]

[0128] As shown in Tables 1 to 4, dental compositions containing glass that contains silicon (Si) and cesium (Cs) and is substantially free of sodium (Na), potassium (K), and alkaline earth metals had good storage stability and X-ray contrast properties (Examples 1 to 3).

[0129] In contrast, dental compositions formulated with glass or silica filler that does not satisfy the condition of containing silicon (Si) and cesium (Cs) and being substantially free of sodium (Na), potassium (K) and alkaline earth metals had poor storage stability or X-ray contrast properties (Comparative Examples 1 to 6).

[0130] Although an embodiment of the present invention has been described above, the present invention is not limited to a specific embodiment, and various modifications and changes are possible within the scope of the invention described in the claims.

Claims

1. Contains silicon (Si) and cesium (Cs), Substantially free of sodium (Na), potassium (K) and alkaline earth metals; Dental glass composition.

2. Contains silicon (Si) and cesium (Cs), Substantially free of sodium (Na), potassium (K), barium (Ba) and calcium (Ca); Dental glass composition.

3. A dental glass composition according to claim 1 or 2, and an acidic group-containing polymerizable monomer, Dental compositions.

Citation Information

Patent Citations

  • Chrominance signal processing circuit

    JP1988046086A